Symptomatic intracerebral hemorrhage after non-emergency percutaneous coronary intervention: Incidence, risk factors, and association with cardiovascular outcomes - Lim, Mervyn Jun Rui; Zheng, Yilong; Soh, Rodney Yu-Hang; Foo, Qi Xuan Joel; Djohan, Andie Hartanto; Nga Diong Weng, Vincent; Ho, Jamie Sin-Ying; Yeo, Tseng Tsai; Sim, Hui-Wen; Yeo, Tiong-Cheng; Tan, Huay-Cheem; Chan, Mark Yan-Yee; et al. (Frontiers in Cardiovascular Medicine, 2022)
Objective: To investigate the incidence, risk factors, and association with cardiovascular outcomes of patients who developed symptomatic intracerebral hemorrhage (ICH) after non-emergency percutaneous coronary intervention (PCI). Methods: We conducted a single-institution retrospective study of patients who developed symptomatic ICH after non-emergency PCI. To identify associations between clinical variables and outcomes, logistic regression and Cox-proportional hazards regression models were constructed. Outcomes analyzed include (1) all-cause mortality, (2) acute ischemic stroke (AIS) or transient ischemic attack (TIA), and (3) major adverse cardiovascular events (MACE). Results: A total of 1732 patients were included in the analysis. The mean (±SD) age was 61.1 (±11.3) years, and 1396 patients (80.6%) were male. The incidence of symptomatic ICH after non-emergency PCI was 1.3% (22 patients). Age, chronic kidney disease, and prior coronary artery bypass graft surgery were independently associated with a higher risk of ICH after PCI, while hyperlipidemia was independently associated with a lower risk of ICH after PCI. ICH after PCI was independently associated with a higher risk of all-cause mortality and AIS or TIA after PCI. Conclusion: Patients who are older, who have chronic kidney disease, and who have had prior coronary artery bypass graft surgery should be monitored for symptomatic ICH after non-emergency PCI.